The Chest Australia Trial: a randomised controlled trial of an intervention to increase consultation rates in smokers at risk of lung cancer. Issue 4 (10th January 2019) - Emery, Jon D; Murray, Sonya R; Walter, Fiona M; Martin, Andrew; Goodall, Stephen; Mazza, Danielle; Habgood, Emily; Kutzer, Yvonne; Barnes, David John; Murchie, Peter
Abstract : Background: International research has focused on screening and mass media campaigns to promote earlier patient presentation and detect lung cancer earlier. This trial tested the effect of a behavioural intervention in people at increased risk of lung cancer on help-seeking for respiratory symptoms. Methods: Parallel, individually randomised controlled trial. Eligible participants were long-term smokers with at least 20 pack-years, aged 55 and above. The CHEST intervention entailed a consultation to discuss and implement a self-help manual, followed by self-monitoring reminders to encourage help-seeking for respiratory symptoms. The control group received a brief discussion about lung health. Both groups had baseline spirometry. Telephone randomisation was conducted, 1:1, stratified Medical Research Council (MRC) dyspnoea score and general practice. Participants could not be blinded; data extraction and statistical analyses were performed blinded to group assignment. The primary outcome was respiratory consultation rates. Results: We randomised 551 participants (274 intervention, 277 control) from whom the primary outcome was determined for 542 (269 intervention, 273 control). There was a 40% relative increase in respiratory consultations in the intervention group: (adjusted rates (95% CI) intervention 0.57 (0.47 to 0.70), control 0.41 (0.32 to 0.52), relative rate 1.40 (1.08 to 1.82); p=0.0123). There were no significant differences in time to first respiratory consultation, total consultation rates or measures of psychological harm. The incremental cost-effectiveness ratio was $A1289 per additional respiratory consultation. Conclusions: A behavioural intervention can significantly increase consulting for respiratory symptoms in patients at increased risk of lung cancer. This intervention could have an important role in primary care as part of a broader approach to improve respiratory health in patients at higher risk. Trial registration number: Australian New Zealand Clinical Trial Registry (1261300039 3752). This was registered pre-results.